Problematika Waris Bagi Anak Hasil Nikah Siri Perspektif Hukum Keluarga Islam (Studi Putusan MK No. 46/PUU-VIII/2010) - Sukmawati; Ahmad Junaidi (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: This article aims to examine the rights and position of children resulting from unregistered marriages in the Constitutional Court decision No.46/PUU-VIII/2010 based on Islamic family law, as well as the status of inheritance rights of children resulting from unregistered marriages according to Constitutional Court decision No.46/PUUVIII/2010. This research uses a type of normative legal research with a statutory approach, case studies and conceptual approaches. The results of this research show that firstly, the Constitutional Court's decision provides legal protection for children who have been born in an unregistered marriage between their parents. This has a legal impact, that the child has a civil relationship with the father. Second, in Islamic inheritance law, the conditions and pillars of a marriage that have been carried out in accordance with the Shari'a become a valid marriage, even though in this era registration is required. This does not invalidate the lineage to the father, because the lineage relationship is formed from a siri marriage which is valid according to the pillars and terms of marriage.Keywords: Inheritance, Children Resulting from Siri Marriage, Islamic Family Law. Abstrak: Tulisan ini bertujuan untuk mengkaji hak serta kedudukan anak hasil kawin siri dalam putusan MK No.46/PUU-VIII/2010 berdasarkan hukum keluarga Islam, serta status hak waris anak hasil kawin siri sesuai putusan MK No.46/PUU-VIII/2010. Penelitian ini menggunakan jenis penelitian hukum normatif dengan pendekatan perundang-undangan, studi kasus, dan pendekatan konseptual. Hasil penelitian ini menunjukkan bahwa pertama pada putusan MK tersebut memberikan perlindungan hukum terhadap anak yang telah dilahirkan atas perkawinan siri oleh kedua orang tuanya. Hal tersebut memberikan dampak hukum, bahwa anak memiliki hubungan keperdataan dengan bapak. Kedua dalam hukum waris Islam bahwa syarat dan rukun perkawinan yang telah dilaksanakan sesuai syariat menjadi perkawinan yang sah kendati pada era ini diperlukan pencatatan. Hal tersebut tidak membatalkan nasab kepada bapak, karena hubungan nasab terbentuk dari perkawinan siri yang sah menurut rukun dan syarat perkawinan.Kata Kunci: Waris, Anak Hasil Nikah Siri, Hukum Keluarga Islam.